Genomic characterization of an NDM-9-producing Acinetobacter baumannii clinical isolate and role of Glu152Lys substitution in the enhanced cefiderocol hydrolysis of NDM-9 - Gaillot, Susie; Oueslati, Saoussen; Vuillemenot, Jean-Baptiste; Bour, Maxime; Iorga, Bogdan I.; Triponney, Pauline; Plésiat, Patrick; Bonnin, Rémy A.; Naas, Thierry; Jeannot, Katy; Potron, Anaïs (Frontiers in Microbiology, 2023)
Here, we characterized the first French NDM-9-producing Acinetobacter baumannii isolate.A. baumannii 13A297, which belonged to the ST Pas 25 (international clone IC7), was highly resistant to b-lactams including cefiderocol (MIC >32 mg/L). Whole genome sequencing (WGS) using both Illumina and Oxford Nanopore technologies revealed a 166-kb non-conjugative plasmid harboring a blaNDM-9 gene embedded in a Tn125 composite transposon.Complementation of E. coli DH5a and A. baumannii CIP70.10 strains with the pABEC plasmid carrying the blaNDM-1 or blaNDM-9 gene, respectively, resulted in a significant increase in cefiderocol MIC values (16 to >256-fold), particularly in the NDM-9 transformants.Interestingly, steady-state kinetic parameters, measured using purified NDM-1 and NDM-9 (Glu152Lys) enzymes, revealed that the affinity for cefiderocol was 3-fold higher for NDM-9 (Km = 53 µM) than for NDM-1 (Km = 161 µM), leading to a 2-fold increase in catalytic efficiency for NDM-9 (0.13 and 0.069 µM -1 .s -1 , for NDM-9 and NDM-1, respectively). Finally, we showed by molecular docking experiments that the residue 152 of NDM-like enzymes plays a key role in cefiderocol binding and resistance, by allowing a strong ionic interaction between the Lys152 residue of NDM-9 with both the Asp223 residue of NDM-9 and the carboxylate group of the R1 substituent of cefiderocol.